Research status of ambulatory blood glucose monitoring in patients with type 2 diabetes mellitus (动态血糖监测在2型糖尿病患者中应用研究现状) - LIU MingLei (刘明磊); WU Quanying (武全莹); YU Shuyi (于淑一) (中西医结合护理)
Dynamic blood glucose monitoring system (CGMS) can monitor the blood glucose of patients with diabetes for many consecutive days and provide dynamic blood glucose monitoring maps, it has been widely used in clinic, which provides reliable data for doctors to understand the blood glucose fluctuations of patients, especially asymptomatic hypoglycemia at night. This paper reviewed the studies about principle of CGMS, application advantages in the treatment of type 2 diabetes mellitus and application status in the clinical setting, in order to provide reference to the treatment of nursing of patients with type 2 diabetes mellitus. (动态血糖监测系统(CGMS)可对糖尿病患者实行连续的血糖监测, 提供动态血糖图谱, 为医务人员的诊疗提供可靠的依据。本研究就CGMS的原理、在T2DM患者治疗中的应用优势和现状进行综述, 旨在为T2DM患者的治疗和护理提供可靠参考。)